Ectosomes: a new mechanism for non-exosomal secretion of tau protein. - Simon Dujardin (Public Library of Science (PLoS), 2014)
Tau is a microtubule-associated protein that aggregates in neurodegenerative disorders known as tauopathies. Recently, studies have suggested that Tau may be secreted and play a role in neural network signalling. However, once deregulated, secreted Tau may also participate in the spreading of Tau pathology in hierarchical pathways of neurodegeneration. The mechanisms underlying neuron-to-neuron Tau transfer are still unknown; given the known role of extra-cellular vesicles in cell-to-cell communication, we wondered whether these vesicles could carry secreted Tau. We found, among vesicles, that Tau is predominately secreted in ectosomes, which are plasma membrane-originating vesicles, and when it accumulates, the exosomal pathway is activated.